Mengaktualisasikan Potensi Siswa Berbakat di Sekolah Unggulan melalui Layanan Bimbingan dan Konseling Khusus - Abdul Hadis (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2003)
This globalized era is signified with competitions in almost all life sectors. Winning the competitions needs excellent human resources, and one of the competitive human resources is talented individuals. These talented individuals, however, needs specific education and guidance which can help them realize their talents optimally. Therefore, specific education and guidance should be given early on to facilitate them to realize their excellent talents.